Compendium of Selected Characteristics of the Kentucky State-Supported Institutions of Higher Education, 1960-1969 - Kentucky Council on Public Higher Education, Frankfort; Kentucky Council on Public Higher Education, Frankfort ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This report contains statistical information on Kentucky public institutions of higher education and includes data on: (1) enrollment and general fund appropriations 1959-60 through 1969-70 by institution and in toto; (2) total resident and non-resident student enrollment, and resident and non-resident enrollment by institution and by classification; (3) freshmen matriculation in toto and by institution; (4) Fall 1969 freshmen admission in toto and by institution; (5) academic deficiency and the freshmen class of 1968; (6) financial aid applications received from full-time freshmen at the six state-supported institutions in Fall 1969; (7) degrees earned, 1960-1969, in toto and by institution; (8) degree programs offered at the six state-supported institutions and the University of Louisville; and (9) capital construction, 1960-1970. (AF)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Financial Needs; College Freshmen; Degrees (Academic); Enrollment; Higher Education; Statistical Data; Kentucky